2010
DOI: 10.1089/cbr.2010.0811
|View full text |Cite
|
Sign up to set email alerts
|

Association ofXRCC1Variants with Acute Skin Reaction After Radiotherapy in Breast Cancer Patients

Abstract: After irradiation results in cytotoxic effects by DNA damage, base excision repair (BER) pathway is involved in the repair of single-strand breaks and nonhomologous end joining and homologous repair of double-strand breaks caused by radiotherapy. Alterations in the function of BER DNA repair genes may affect DNA repair proficiency and influence the response of patients with cancer to radiotherapy. The association of single nucleotide polymorphisms of BER DNA repair X-ray repair cross-complementing group 1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…After application of critical search strategies and exclusion criteria, 11 follow-up studies (Moullan et al, 2003;Chang-Claude et al, 2005;Brem et al, 2006;Giotopoulos et al, 2007;Chang-Claude et al, 2009;Zhou et al, 2010;Zschenker et al, 2010;Mangoni et al, 2011;Falvo et al, 2012;Raabe et al, 2012;Terrazzino et al, 2012) comprising 2199 cases were eligible for the present analysis. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After application of critical search strategies and exclusion criteria, 11 follow-up studies (Moullan et al, 2003;Chang-Claude et al, 2005;Brem et al, 2006;Giotopoulos et al, 2007;Chang-Claude et al, 2009;Zhou et al, 2010;Zschenker et al, 2010;Mangoni et al, 2011;Falvo et al, 2012;Raabe et al, 2012;Terrazzino et al, 2012) comprising 2199 cases were eligible for the present analysis. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The baseline characteristics of the included studies are shown in Table 1. Ten of these studies included mainly Caucasian patients and one study included only Chinese patients (Zhou et al, 2010). All of them were published in English-language journals.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations